Photography as an illustration method of an album book - Guadamuz Villalobos, Jairo Andrés (2020)
The close relationship between the text and the image is studied, with special attention to the illustrated works called the album book. It also addresses the role that the image plays in cognitive processes, as well as its discursive and narrative role. A historical review is made about photography, and its ability to reproduce reality is studied. From these reflections, the importance of the image in reading animation is discussed and emphasis is placed on the use of photography as a method of illustration for literary works. In addition, the process of re-illustration of the work The Guardian of Nature and her friends save the river is described, through the reproduction at scale of her characters and scenarios for the subsequent capture of them. It also details the process of diagramming the work and the final product obtained.